2023
DOI: 10.1038/s41598-022-27345-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate contamination in drinking water and adverse reproductive and birth outcomes: a systematic review and meta-analysis

Abstract: Exposure to low levels of nitrate in drinking water may have adverse reproductive effects. We reviewed evidence about the association between nitrate in drinking water and adverse reproductive outcomes published to November 2022. Randomized trials, cohort or case–control studies published in English that reported the relationship between nitrate intake from drinking water and the risk of perinatal outcomes were included. Random-effect models were used to pool data. Three cohort studies showed nitrate in drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Finally, we did not investigate other adverse pregnancy outcomes that have been linked to drinking water contamination, such as prematurity and low birthweight. 36,37 DPR may increase efficiency and sustainability while reducing costs and wastewater discharge, 38 but concerns regarding the safety and acceptability of this approach remain. Importantly, the lack of an environmental buffer could conceivably result in increased concentrations of contaminants that have been linked to birth defects and adverse pregnancy outcomes in treated drinking water.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not investigate other adverse pregnancy outcomes that have been linked to drinking water contamination, such as prematurity and low birthweight. 36,37 DPR may increase efficiency and sustainability while reducing costs and wastewater discharge, 38 but concerns regarding the safety and acceptability of this approach remain. Importantly, the lack of an environmental buffer could conceivably result in increased concentrations of contaminants that have been linked to birth defects and adverse pregnancy outcomes in treated drinking water.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review involving a sample of over 7 million subjects found nitrate in drinking water to be associated with a host of adverse reproductive and birth outcomes, including an increased risk of preterm birth, at nitrate levels below the current regulatory levels. 5 Some case studies also showed that nitrate in drinking water may be associated with an increased risk of neural tube defects (NTDs), although the result does not appear to be robust across samples. As with other correlational analyses, caution is warranted in interpreting results as causal or in making quantitative inferences about the magnitude of impacts.…”
Section: N Itroge Nmentioning
confidence: 99%
“…Because of the large amount of nitrogenous wastewater discharged from agriculture and industry and the extremely high solubility of NO 3 − in water, the nitrogen cycle in ecosystems has been severely disrupted, thereby endangering human health. 1 Therefore, numerous researchers are striving to restore balance to the nitrogen cycle. [2][3][4] Common NO 3 − removal methods include physical, biological, and chemical methods.…”
Section: Introductionmentioning
confidence: 99%